Three years of barrier cover field trials at Rosebery mine - Rohde, T.; Vogler, H.; Lang, J.; Crosbie, J.; Pandelis, A. (Mine Closure 2024: Proceedings of the 17th International Conference on Mine Closure, 2024)
The MMG Rosebery mine is located on the west coast of Tasmania, Australia, approximately (~) 125 km south of Burnie and ~300 km northwest of Hobart. The mine is an underground polymetallic operation (zinc, lead, copper, gold and silver) with some small-scale open cut workings. The Bobadil tailings storage facility (TSF) contains mine tailings that are potentially acid forming (PAF). Rehabilitation of a PAF TSF to minimise environmental contamination is site specific; being a function of, among other factors, construction, the tailings deposition method and climate. The primary design objective of the cover is to limit rainfall infiltration (percolation), with a secondary objective of limiting the ingress of oxygen into the underlying PAF tailings. Two experimental barrier covers (the options) have been constructed in preparation for comparison to decide on a suitable cover. Both options include layers of moorland peat and glacial till; however, one option includes a geosynthetic clay liner (GCL) between the glacial till and tailings. The results indicate that the moorland peat layer provides a perched phreatic zone that is largely anoxic. It limits the potential for deep-rooted trees, which could damage the GCL, to establish. It also provides the preferred environment for shallow-rooted native grasses. Shallow-rooted grasses enhance cover water movement and create an ecological community that is sympathetic to the surrounding landscape. The purpose of this paper is to describe the method and results for the cover trials that are being used to assess the performance of each option.